Staying with the Planet - Çelik, Leman; Laser, Stefan; Sørensen, Estrid; Abels, Sandra (transcript Verlag, 2026)
Hidden from view, university data infrastructures circulate, process and store scientific data while requiring extensive energy and metal extraction. The authors of this volume offer a speculative engagement with cultures of scientific competition, institutional habits, server procurement and regulations, and with funding procedures that each in different ways contribute to scientific computing and its planetary effects. Short speculative ethnographic texts and original line art offer witty and thought-provoking takes on the challenges data-driven science faces in times of climate change.